RESPONSIVENESS OF SOCIAL VALUES AND REAL GROSS DOMESTIC BRUTO ON MONEY DEMAND IN INDONESIA - Aditia, Maulana Rifki; Cahyono, Eko Fajar (Journal of Islamic Monetary Economics and Finance, 2018)
The purpose of this study was to determine the effect, estimates shocks and determine the contribution of , social values, real GDP currency, demand deposits wadi'ah, Mudaraba savings, deposits mudaraba and Islamic Bank Returns to money demand in Indonesia. Real GDP and social values theoretically able to increase money demand using each mechanism. Money demand represented by M2 with a composition comprising of fiat money, wadiah demand deposits, mudaraba savings and mudaraba investment deposits completed Islamic Bank return as balancing cost in Money demand. The research method used in this research is comparative quantitative. This research utilizes 8 (eight) variable which then unit root test, determining Lag Optimal, Cointegrate-Test, VECM Estimates, Impulse Response Function and Variance Decomposition are carried out. The results of VECM estimation showed that real GDP, fiat money, wadiah demand deposits, sharia return, mudaraba savings and mudaraba investment deposits are significantly influencing the amount of Money demand in long term. In short term, social values significantly influencing the amount of money demand in Indonesia. The results of Impulse response showed that real GDP positively responded by the M2. Then, social values positively responded, fiat money positively responded, wadiah deposits positively responded, mudaraba savings negatively responded, mudaraba deposits positively responded and sharia return positively responded by the M2IS. Variance decomposition results showed that social values has the biggest contribution, then followed by demand deposits wadi'ah, mudaraba deposits, mudaraba savings, currency, real GDP and return sharia smallest.